The role of the Woźniak family in the socio-economic life of Sosnowiec. A case study. (Zaranie Śląskie, 2025)
The Woźniak family from Sosnowiec, although they played an important role in the socio-economic life of the city, is somewhat forgotten today, even by native residents. In 2024, the Schoen Palace Museum in Sosnowiec will enrich its collections with the very valuable and interesting "Woźniak Archive" - ​​a collection of over 400 photos and over 70 documents and private letters, which provide new information about the history of the family, especially its private life. The history of the Woźniaks begins in 1885, when Jan and Małgorzata came to Sosnowiec. Jan started working in the steelworks, and Małgorzata ran a beer bar. Their three sons - Franciszek, Teodor and Andrzej - received technical education, which, after their father's death, allowed the family to establish a metal plant on the border of Stary Sosnowiec and Pogoń, the Woźniak Steel Foundry Małgorzata and Sons. The intensive development was halted by World War I, when the Germans occupied the factory for military purposes.After regaining independence, the Woźniaks rebuilt the foundry, which became one of the pillars of the local industry. During the Silesian Uprisings, the plant became famous as the place where two armored combat vehicles were assembled, which took part in the fighting. In the interwar period, "Stalownia Woźniak" developed, transforming into a joint-stock company. The time of prosperity was interrupted by the Great Depression and family conflicts, which ended in court.During the Nazi occupation, the factory was taken over by the Germans and used for war production. After the war, the plant was nationalized.Research into the history of the Woźniak family was based not only on newly acquired collections, but also on documents stored in state archives and the press.
Keywords: Sosnowiec; Zaglebie Dabrowskie; industrial history; The Woźniaks from Sosnowiec; iron casting